Persianate Islamic Sphere: Peran Bangsa Persia dalam Konstelasi Islam Kontemporer melalui Pendekatan Tipologi Kawasan - Ahmad Sulton Ariwibowo; Anis Humaidi; Ahmad Subakir (JOM, 2025)
The construction of the Persianate Islamic Sphere as an analytical framework to understand the role of the Persian people in contemporary Islamic contemplation through a regional typology approach. The study is positioned within the disciplinary discourses of Islamic area studies, intellectual history, and political anthropology. The purpose of this article is to identify the characteristics of the Persian region covering Iran, Afghanistan, and Pakistan and to trace how Persian cultural heritage has shaped patterns of Islamization, scholarly traditions, and socio-religious practices in the modern era. This research employs a qualitative method with data collected through literature review, historical document analysis, and examination of recent academic publications; the data sample includes classical Persian texts, works of contemporary scholars, and scholarly reports on religious dynamics in the region. The working hypothesis posits that the Persian region exhibits a distinctive developmental pattern of Islam different from both the Arab world and South Asia. The findings indicate that the Persian regional typology is marked by cultural continuity, strong intellectual traditions, and dynamic interactions among state, religion, and ethnicity. This article contributes to strengthening regional perspectives within contemporary Islamic studies. The results highlight the importance of understanding Persia as a significant center of Islamic contemplation in the modern religious landscape.